A survey study on knowledge of alzheimer’s disease (AD) among phamacists in Selangor / Thimarul Huda Mat Nuri - Mat Nuri, Thimarul Huda (2017)
Background: Alzheimer’s disease (AD) is the most common cause of dementia. There are about 50,000 people in Malaysia who suffer from the disease and most of them are not diagnosed. Pharmacists are a part of the healthcare team, however the depth of their knowledge in managing AD is unknown and some of them handle AD patients without specializing in neurology and geriatry. This study is to assess the level of AD knowledge among pharmacists in health clinics and hospitals and to identify the relationship between demographic characteristics and the knowledge of AD. Method: Questionnaire consisting of demographic backgrounds and a validated 30 items- Alzheimer disease knowledge scale (ADKS) tool was used to assess AD knowledge. There were 7 health clinics and 9 hospitals recruited by convenience sampling and manual surveys were distributed to nearby healthcare clinics and hospitals. For the pharmacists working in distant areas, email was used to distribute the questionnaires. The score was compared and evaluated across demographics categories. Results: 445 pharmacists were obtained with diverse demographic background, the overall total mean score was 18.76(3.62): for healthcare professionals the mean score was 19.05(3.69) and for hospitals it was 18.47(3.56).Generally the level of AD knowledge was moderate and there was no difference in AD knowledge between pharmacists in health clinics and hospitals (p= 0.095). For the individual ADKS domain, there was significant result shown in care giving (p=0.033) where hospital pharmacists possessed higher scores than health clinics, domains of symptoms and course of disease were shown to have the lowest score. These two domains are more medical-oriented, whilst treatment and care giving had the highest score. TPN and Outpatients unit had the highest score. However the TPN sample was too small so it may not represent the real population of the TPN unit. Clinical pharmacists which have direct contact with patients had lower scores than outpatient pharmacists and this suggests that AD patients are usually treated as outpatients. Three independent predictors were found in this study: Malays ethnicity, aged less than 30 and outpatients’ pharmacists. These three independent variables gave positive relationship to AD score. Conclusion: Majority AD knowledge among pharmacists in Selangor was at a moderate level. Malay, outpatient pharmacists and those respondents aged less than 30 scored the highest. Limitations in this study were the background on training and experience on AD should be incorporated so that the findings can be more accurate in evaluating the AD knowledge individually. This study suggests and supports the suggestion for ongoing education and training programme on AD for pharmacists in various disciplines.